Pengaruh Integritas, Kompetensi, dan Independensi Auditor Terhadap Kualitas Audit (Studi Empiris Inspektorat Daerah Provinsi Banten) - Cucu Elyasinta (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
The research is aimed to know the effect of integrity, competence, and independence on audit quality in the Inspectorate of Banten province regional inspectorate. The data were gained based onquestionnaires distributed to 66 respondents that were chosen using purposive sampling. The analysis method involved multiple linear regression analysis using SPSS v25. In this research, the dependent variable is audit quality and independent variable consisted of integrity, competence, and auditors independence. The results showed that competence do not affect audit quality, while integrity, and independence, affect the quality of audits of Banten province regional inspectorate.